Cognitive psychology - Coxon, Matthew (Thousand Oaks, Calif. : SAGE, 2012)
'This accessible text addresses the core knowledge domain of cognitive psychology, with focused coverage of the central concepts, research and debates in this key area. The engaging text provides detailed information on thinking and reasoning, learning and memory, language, perception, attention, and consciousness. A final chapter examines cognitive neuropsychology. There is an emphasis on the way the properties of cognition relate to our everyday lives. Learning features including case studies, research summaries, short review questions and assignment topics, are provided throughout to aid students' understanding and promote a critical approach. In addition extended critical thinking and skill builder activities develop the reader's higher level skills.'--Publisher's website.
Includes bibliographical references (p. 153-165) and index.
Keywords: Cognitive psychology